Effects of PCSK9 inhibitors on HDL cholesterol efflux and serum cholesterol loading capacity in familial hypercholesterolemia subjects: a multi-lipid-center real-world evaluation - Palumbo, Marcella; Giammanco, Antonina; Purrello, Francesco; Pavanello, Chiara; Mombelli, Giuliana; Di Pino, Antonino; Piro, Salvatore; Cefalù, Angelo Baldassare; Calabresi, Laura; Averna, Maurizio; Bernini, Franco; Zimetti, Francesca; et al. (Frontiers in Molecular Biosciences, 2022)
Proprotein convertase subtilisin/kexin type 9 (PCSK9), beyond regulating plasma LDL cholesterol (LDL-c), exerts several pleiotropic effects by modulating lipid metabolism in extrahepatic cells such as macrophages. Macrophage cholesterol homeostasis depends on serum lipoprotein functions, including the HDL capacity to promote cell cholesterol efflux (CEC) and the serum capacity to promote cell cholesterol loading (CLC). The aim of this observational study was to investigate the effect of PCSK9 inhibitors (PCSK9-i) on HDL-CEC and serum CLC in patients with familial hypercholesterolemia (FH). 31 genetically confirmed FH patients were recruited. Blood was collected and serum isolated at baseline and after six months of PCSK9-i treatment. HDL-CEC was evaluated through the main pathways with a radioisotopic cell-based assay. Serum CLC was assessed fluorimetrically in human THP-1 monocyte-derived macrophages. After treatment with PCSK9-i, total cholesterol and LDL-c significantly decreased (-41.6%, p<0.0001 and -56.7%, p<0.0001, respectively). Total HDL-CEC was not different between patients before and after treatment. Conversely, despite no changes in HDL-c levels between the groups, ABCG1 HDL-CEC significantly increased after treatment (+22.2%, p<0.0001) as well as HDL-CEC by aqueous diffusion (+7.8%, p=0.0008). Only a trend towards reduction of ABCA1 HDL-CEC was observed after treatment. PCSK9-i significantly decreased serum CLC (-6.6%, p=0.0272). This effect was only partly related to the reduction of LDL-c levels. In conclusion, PCSK9-i treatment significantly increased HDL-CEC through ABCG1 and aqueous diffusion and reduced the serum CLC in FH patients. The favorable effect of PCSK9-i on functional lipid profile could contribute to the cardiovascular benefit of these drugs in FH patients.